Corn Transformation Machine as Media Increases Threshing Productivity of Corn Village Prupuh, Panceng Sub - District, Gresik Regency - Syaifudin, Syaifudin; Firmansyah, Muhammad Wahyu; Zainuri, Muhammad; Anggraeni, Siska; Romadhon, Muhammad Wahyu; A, Fery , Lasiyano; C, Dimas Eko; I, Rosikhul Islah; Mukramin, Baso (Kontribusia : Research Dissemination for Community Development, 2019)
Prupuh village is a village in the district Panceng by having a hamlet that Hamlet Prohibition. 2000 more residents in the village Prupuh with 575 heads of household, and 400 homes were built. In general livelihoods of the majority of the villagers are farmers Prupuh. In the rainy season corn is one of the crops grown by the residents both in the fields and in the yard. Corn Transformation Machine addressed to the villagers of Prupuh that planting corn with manual harvesting. People have become less productive because of the time needed to separate the corn from bongkolnya very long. From the experimental results using Corn Transformation Machine tool time needed to separate the corn seed from bongkolnya ie 30 seconds per 1 piece of corn, while if using a hand (manual) takes 5 minutes per 1 piece of corn. The tool can save time for 4.5 minutes and simultaneously increase productivity the amount of corn kernels are separated from bongkol.